Luciferase-free Luciferin Electrochemiluminescence - Belotti, Mattia; El-Tahawy, M.M.T.; Yu, L.J.; Russell, I.C.; Darwish, Nadim; Coote, M.L.; Garavelli, M.; Ciampi, Simone (WILEY-V C H VERLAG GMBH, 2022)
Luciferin is one of Nature's most widespread luminophores, and enzymes that catalyze luciferin luminescence are the basis of successful commercial “glow” assays for gene expression and metabolic ATP formation. Herein we report an electrochemical method to promote firefly's luciferin luminescence in the absence of its natural biocatalyst—luciferase. We have gained experimental and computational insights on the mechanism of the enzyme-free luciferin electrochemiluminescence, demonstrated its spectral tuning from green to red by means of electrolyte engineering, proven that the colour change does not require, as still debated, a keto/enol isomerization of the light emitter, and gained evidence of the electrostatic-assisted stabilization of the charge-transfer excited state by double layer electric fields. Luciferin's electrochemiluminescence, as well as the in situ generation of fluorescent oxyluciferin, are applied towards an optical measurement of diffusion coefficients.